Hospital Preaching As Informed by Bedside Listening: A Homiletical Guide for Preachers, Pastors, and Chaplains in Hospital, Hospice, Prison, and Nursing Home Ministries - Ihewulezi, Cajetan N. (Hamilton Books, 2010)
Hospital Preaching as Informed by Bedside Listening states the great need to sit down face to face and attentively listen to stories, experiences, and feelings of patients. These bedside encounters with patients can well inform the preacher (chaplain or pastoral minister) and can result in more effective liturgical preaching in hospitals, hospice, prison, and nursing home settings. This book aims to improve pastoral care ministry of the sick. This pastoral approach provides a homiletical guide for preachers, pastors, and chaplains involved in hospital, hospice, or nursing home ministries. It also helps pastoral ministers to develop better listening skills for the stories and experiences of the sick, as well as the ability to use these stories and experiences in the proclamation of the gospel. Such intentional bedside listening and the preaching that results from listening are important for addressing the problems of the sick and can enhance emotional, spiritual, and physical healing.